Technology-based solutions for behavior monitoring: lessons learned - Pandria, Niki; Bamidis, Panagiotis D. (Frontiers in Education, 2023)
Introduction: Children’s behavior is indicative of adaptation to early age development. Adaptive difficulties linked to behavioral difficulties are frequent among school-aged children having a multi-level impact. Five key approaches have been used therapeutically while systematic behavior monitoring has been used to evaluate the efficacy of different interventions. The inherent barriers of traditional monitoring tools have led to the need to design and implement new approaches. Methods: Four case study series (S1-S4) focused on vulnerable populations are described. Eight participants with different medical backgrounds underwent an intervention, either cognitive training (BrainHQ) (7 out of 8) or operant conditioning strategies. Targeted behaviors were monitored in 6 out of 8 participants using WHAAM application which could also measure the effect of the intervention applied, while emotional fluctuations were evaluated in 2 out of 8 participants using AffectLecture. Moreover, a 5th pilot study (S5) is included focusing on early detection and management of ADHD using a serious game-based platform. Results: In S1, monitoring highlighted that BrainHQ training resulted in positive changes in all but one of the behaviors in Case 1. Studies that exploited the AffectLecture application indicated that emotional state was improved after training, and it was positively correlated with the performance in cognitive exercises. The performance in cognitive training was positively correlated with emotional state before training in S2 but not in S3. A positive correlation between the change in emotional state and performance was mentioned only in S3. Educational, and social benefits as well as a positive correlation between the performance and the length of training were reported in both studies. Operant conditioning strategies in S4 resulted in positive behavioral effects in most participants. Preliminary analysis of S5 indicated that the platform has a considerable capacity to discriminate users based on their in-game patterns as ADHD or non-ADHD. Discussion: The mixture of studies presented in this paper incorporate different technological solutions for monitoring or intervening in developmental disorders and behavioral difficulties. Despite the inherent inhomogeneity of such an endeavor, they all highlight the positive prospects of using technology to enhance the educational arsenal of facing behavioral and learning difficulties.